Pakej pembelajaran bermultimedia untuk kanak-kanak prasekolah: Mengenal objek & warna / Le Chew Fang - Le, Chew Fang (2002)
Thesis is one of the compulsory subject that must be taken by final year's students. The motive is to test the skill of analyst and design when develop a project. The project that will be developed is a package learning "Mengenal Objek dan Warna". It is a multimedia learning package which will integrate animation, graphics, audio, video and text to produce a more effective learning environment. Target of the user for this package is the preschool children, aged from 3-7 years old. This learning package will be developed in two languange which is Malay and English. It is more on teaching children on how to recognize the object and colour that appear around us. Beside that the package also provide kuiz corner and entertainment corner so that children will not feel boring along the period of learning. The way of teaching will be more interactive such as teaching them through the games or stories. This package is developed to meet the needs of parent as the teaching tools in the school. Together with the government exclamation to produce more citizens with literate computer, this is the best way to start it from the preschool children. Through this package, children will be teach on how to use a computer or a basic of using computer such as using keyboard. This package is developed using Macromedia Director 8.0 and other utility programme such a Adobe Photoshop and Paint Shop to produce a more interactive animation. This report will describe each of the process that involved in development of the learning package. It also include diagram and chart as reference.